Analisis Penerapan Sistem Informasi Terhadap Efektivitas Kerja - Ndruru, Yunius; Zebua, Dermawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of information technology encourages organizations to implement information systems to improve employee work effectiveness. Information systems not only function as data processing tools, but also as a means of supporting decision-making and improving organizational performance. This study aims to analyze the effect of information system implementation on employee work effectiveness. The research method used is a quantitative method with a descriptive and verification approach. Data collection was carried out by distributing questionnaires to employees who use information systems in carrying out their work. Data were analyzed using simple and multiple linear regression analysis. The results of the study indicate that the implementation of information systems has a positive and significant effect on employee work effectiveness. Information systems that are easy to use, accurate, and timely can increase work speed, accuracy of results, and efficiency of resource use. Thus, the optimal implementation of information systems can be an important factor in improving employee work effectiveness.